Semiclassical Theory of Stepped Electrodes and Step Bunching - Zengming Zhang; Michael Eikerling; Jun Huang (Journal of the American Chemical Society, 2026)
Abstract Atomic-scale steps markedly influence electrochemical activity and stability and exhibit structural instability under electrochemical conditions. Yet the microscopic mechanisms that cause these behaviors remain largely unclear. Herein, we study the microstructure and thermodynamics of the electrical double layer at stepped electrodes, using the semiclassical density-potential functional theory. The theory captures trends observed in experiments regarding the differential capacitance and the potential of zero free charge (PZFC) with step density for stepped Au and Ag . Departing from the case of flat electrodes, the PZFC deviates from the potential of minimum capacitance at stepped electrodes, necessitating local PZFCs to describe heterogeneous surface charging conditions. Furthermore, linking step-induced PZFC shifts to changes of the surface tension, the theory predicts that step bunching is thermodynamically driven at more positive electrode potentials and sensitive to the electrolyte composition.